Selective expression of endogenous lactose-binding lectins and lactoseries glycoconjugates in subsets of rat sensory neurons. - Regan, L J (1986)
Cell-surface glycoconjugates and endogenous lectins have been implicated in cellular interactions that contribute to embryonic development. Functional subsets of primary sensory neurons in mammalian dorsal root ganglia (DRG) have been shown recently to express specific cell-surface oligosaccharide structures. We report here that endogenous lectins with affinity for sensory neuron glycoconjugates are also synthesized by subsets of DRG neurons and are present in the dorsal horn of the developing spinal cord. The distribution of two endogenous lactose-binding lectins, RL-14.5 and RL-29 (subunit Mrs of 14,500 and 29,000, respectively), was examined by immunoblotting and by immunocytochemistry in embryonic and postnatal rat DRG and spinal cord. The two lectins appear soon after the formation of the DRG and are present in the cell bodies and terminals of subsets of DRG neurons that also express cytoplasmic and cell-surface lactoseries glycoconjugates. RL-14.5 and RL-29 are present in overlapping, but not coincident, subsets of DRG neurons that project to the superficial dorsal horn of the spinal cord. In addition, RL-14.5, but not RL-29, is expressed in spinal motoneurons from embryonic day 14. The preferential localization of lactoseries glycoconjugates and lactose-binding lectins in the DRG and the dorsal horn of the spinal cord suggests that these complementary molecules contribute to the development and function of primary sensory neurons.